Analisis Serah Terima Prasarana, Sarana dan Utilitas Perumahan di Kawasan Metropolitan Bandung Raya - Vitriana, Anita (Jurnal Bina Praja, 2019)
There were some problems in the handover of housing Infrastructure, Facilities, and Utilities (PSU (Prasarana, Sarana dan Utilitas)) by developers to local governments. Since the issuance of Minister of Home Affairs Regulation Number 9 of 2009, only small numbers of housing PSU have been handed over by the housing developers to the local government. The objective of this study was to explore some problems related to the handover of the housing PSU which located in Greater Bandung Area, both from the developers and the local governments’ sides. This study used a descriptive - qualitative approach. The primary data collection was conducted with an in-depth interview method to the fourteen developers experienced in housing development in the Greater Bandung Area and three local government officials. The secondary data was collected through the online news along with the regional regulations related to the handover of housing PSU in the districts/cities level of the Greater Bandung Area. The primary and secondary data were analyzed by Qualitative Content Analysis. The study showed that problems came from both developers and local governments’ sides. The developers believed that the bureaucracy for the housing handover was complicated, while the local governments stated there were inconsistencies between the approved site plan and the built PSU. The local governments also have not had mature planning for the housing PSU’s operation and maintenance after the handover. Thus, as the organizer of housing affairs, the governments need to immediately reform the PSU planning and management in terms of its provision, financing, and maintenance.